Benchmark problem in active structural control with wireless sensor network. Issue 1 (23rd May 2015) - Sun, Zhuoxiong; Li, Bo; Dyke, Shirley J.; Lu, Chenyang; Linderman, Lauren
Summary: Structural control systems offer an attractive approach to protect civil infrastructures from natural hazards such as earthquakes. Wireless structural control systems that utilize wireless sensors for sensing, communication, and control have drawn increased attention because of the flexible installation, rapid deployment, and reduced cost. Although there are studies of wireless control systems for civil structures, a benchmark problem that captures not only the dynamics of the plant but also the realistic features of a wireless network has not been available. In this paper, a benchmark model for an active mass driver system with a wireless sensor network is presented. This wireless control benchmark model combines a seismically excited building benchmark model developed with Simulink (Matlab, MathWorks, Inc., Natick, MA, USA) and a wireless sensor network implemented in simulation using a state‐of‐the‐art wireless simulator TOSSIM (UC Berkeley, Berkeley, CA, USA). Wireless signal and noise traces collected from a real‐world multistory building are used as inputs to TOSSIM to realistically simulate the wireless sensor network. Wireless control design issues such as network‐induced delay, data loss, available sensor measurements, measurement noises, and control constraints can be studied with this benchmark model. A sample controller is provided to illustrate the wireless control design. Evaluation criteria have been provided to examine resources and control performances. Copyright © 2015 John Wiley & Sons, Ltd.